2016
DOI: 10.2215/cjn.09050815
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tenapanor on Interdialytic Weight Gain in Patients on Hemodialysis

Abstract: Background and objectives Interdialytic weight gain in patients on hemodialysis is associated with adverse cardiovascular outcomes and increased mortality. The degree of interdialytic weight gain is influenced by sodium intake. We evaluated the effects of tenapanor (AZD1722 and RDX5791), a minimally systemically available inhibitor of the sodium/hydrogen exchanger isoform 3, on interdialytic weight gain in patients with CKD stage 5D treated with hemodialysis.Design, setting, participants, & measurements This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…In patients with CKD, limited sodium excretion owing to impaired kidney function can lead to fluid overload and hypertension and accelerated renal and cardiovascular dysfunction . A study in patients with CKD on dialysis showed no significant differences in interdialytic weight gain (an assessment of fluid overload) between tenapanor‐ and placebo‐treated patients, although the pharmacodynamic effect of tenapanor was confirmed in this patient group, as evidenced by a significant increase in stool sodium and weight in patients treated with tenapanor versus placebo …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In patients with CKD, limited sodium excretion owing to impaired kidney function can lead to fluid overload and hypertension and accelerated renal and cardiovascular dysfunction . A study in patients with CKD on dialysis showed no significant differences in interdialytic weight gain (an assessment of fluid overload) between tenapanor‐ and placebo‐treated patients, although the pharmacodynamic effect of tenapanor was confirmed in this patient group, as evidenced by a significant increase in stool sodium and weight in patients treated with tenapanor versus placebo …”
Section: Discussionmentioning
confidence: 97%
“…By diverting a portion of dietary sodium to the stool, tenapanor treatment results in an increase in stool fluid content and promotes gastrointestinal motility and is therefore being evaluated for the treatment of constipation‐predominant irritable bowel syndrome (IBS‐C) . In patients with CKD, impaired sodium excretion can contribute to fluid overload and accelerated CKD progression; the effect of tenapanor on these processes has been investigated in an additional 2 clinical trials …”
mentioning
confidence: 99%
“…Studies in healthy volunteers and patients with CKD stage 5D have shown that tenapanor treatment increased stool sodium 23,25,26 and phosphorus 26 content, and concomitantly, it reduced urinary sodium 23,26 and phosphorus content, 26 consistent with reduced sodium and phosphate absorption. The precise mechanism by which tenapanor reduces intestinal phosphate absorption is currently under investigation and may allow for a multifaceted approach to reducing phosphate absorption in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Tenapanor acts in the gut to reduce the absorption of sodium and phosphate, with minimal systemic drug exposure. [23][24][25][26] In healthy volunteers, increases in stool phosphorus up to 14.2 mmol/d relative to placebo were observed with tenapanor dosing, with concomitant reductions in urinary phosphorus. 26 The mechanism by which tenapanor reduces GI phosphate uptake is under active investigation; it does not seem to involve direct inhibition of intestinal phosphate transporters type 1 or sodium-dependent phosphate transport protein 2B (NaPi2b, also known as NPT2b).…”
mentioning
confidence: 99%
“…As part of the drug development process, it is important to evaluate potential drug‐drug interactions caused by inhibition or induction of cytochrome P450 enzymes (CYPs) by the investigational agent. Tenapanor has been shown to have minimal systemic availability in all clinical studies to date, including in healthy volunteers and patients with CKD stage 5D treated with dialysis . After oral administration of a single dose of tenapanor 180 mg or tenapanor 15‐90 mg twice daily to healthy Japanese volunteers for 7 days, serum levels of tenapanor were below the lower limit of quantification (0.5 ng/mL) in 567 of 570 postdose samples .…”
mentioning
confidence: 99%